The Influence of Independent Learning, The Use of Google Classroom, and Time Management on Students' Learning Achievement in Economic Subjects - Ratna Nur Aisyah; Pujiati Pujiati; Albet Maydiantoro (Jurnal Pengembangan Profesi Pendidik Indonesia, 2022)
This study aims to determine the effect of learning independence, the use of Google Classroom and time management on student achievement in economics class X Social Sciences SMA Gajah Mada Bandar Lampung. The method in this study uses descriptive verification with ex post facto and survey approaches. The population in this study were active students of class X IPS SMA Gajah Mada Bandar Lampung. The number of samples in this study amounted to 64 students with probability sampling sampling technique using simple random sampling. Data collection uses a questionnaire/questionnaire distributed via Google Forms as a data collection tool. Hypothesis testing was carried out by t and F tests and processed by the SPSS program. The results of the analysis show that there is an effect of learning independence, the use of Google Classroom and time management on student achievement in economics subject class X Social Sciences SMA Gajah Mada Bandar Lampung with a determination level of 0.767 or 76.7% learning achievement is influenced by learning independence, the use of Google Classroom and time management, the remaining 23.3% is influenced by other factors.